2006
DOI: 10.1111/j.1365-2958.2006.05450.x
|View full text |Cite
|
Sign up to set email alerts
|

The exceptionally tight affinity of DnaA for ATP/ADP requires a unique aspartic acid residue in the AAA+ sensor 1 motif

Abstract: SummaryEscherichia coli DnaA, an AAA+ superfamily protein, initiates chromosomal replication in an ATP-bindingdependent manner. Although DnaA has conserved Walker A/B motifs, it binds adenine nucleotides 10-to 100-fold more tightly than do many other AAA+ proteins. This study shows that the DnaA Asp-269 residue, located in the sensor 1 motif, plays a specific role in supporting high-affinity ATP/ADP binding. The affinity of the DnaA D269A mutant for ATP/ADP is at least 10-to 100-fold reduced compared with that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 61 publications
6
76
0
Order By: Relevance
“…Previously, we demonstrated that the DnaA N-terminal domains I-II bind to DiaA (Ishida et al 2004). Domain III and the C-terminal domain IV of DnaA are associated with ATP/ADP-binding and DNA-binding activities, respectively (Erzberger et al 2002;Messer 2002;Fujikawa et al 2003;Kawakami et al 2005Kawakami et al , 2006Kaguni 2006). DiaA stimulated the formation of DnaA multimers on oriC, which stimulated the formation of open complexes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we demonstrated that the DnaA N-terminal domains I-II bind to DiaA (Ishida et al 2004). Domain III and the C-terminal domain IV of DnaA are associated with ATP/ADP-binding and DNA-binding activities, respectively (Erzberger et al 2002;Messer 2002;Fujikawa et al 2003;Kawakami et al 2005Kawakami et al , 2006Kaguni 2006). DiaA stimulated the formation of DnaA multimers on oriC, which stimulated the formation of open complexes.…”
Section: Discussionmentioning
confidence: 99%
“…We next performed a P1 nuclease assay to investigate whether DiaA promoted the formation of the oriC open complex (Kawakami et al , 2006. P1 nuclease specifically degrades single-stranded DNA.…”
Section: Diaa Stimulates Open Complex Formationmentioning
confidence: 99%
See 3 more Smart Citations